2010
DOI: 10.1111/j.1365-313x.2010.04200.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect eggs suppress plant defence against chewing herbivores

Abstract: SUMMARYPlants activate direct and indirect defences in response to insect egg deposition. However, whether eggs can manipulate plant defence is unknown. In Arabidopsis thaliana, oviposition by the butterfly Pieris brassicae triggers cellular and molecular changes that are similar to the changes caused by biotrophic pathogens. In the present study, we found that the plant defence signal salicylic acid (SA) accumulates at the site of oviposition. This is unexpected, as the SA pathway controls defence against fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
293
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(305 citation statements)
references
References 67 publications
8
293
2
2
Order By: Relevance
“…The suppression of maize volatiles invoked by oviposition may therefore be indicative of a manipulative strategy by S. frugiperda to reduce the plants general defensive capacity. One possibility proposed by Bruessow et al (2010) is that oviposition induces salicylic acid (SA)-dependent defenses, which may lead to a suppression of oxylipin-mediated responses to herbivory controlled by the jasmonic acid (JA) pathway. There is ample evidence that jasmonic acid is involved in the induction of maize volatile emissions (Ozawa et al 2000;Schmelz et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of maize volatiles invoked by oviposition may therefore be indicative of a manipulative strategy by S. frugiperda to reduce the plants general defensive capacity. One possibility proposed by Bruessow et al (2010) is that oviposition induces salicylic acid (SA)-dependent defenses, which may lead to a suppression of oxylipin-mediated responses to herbivory controlled by the jasmonic acid (JA) pathway. There is ample evidence that jasmonic acid is involved in the induction of maize volatile emissions (Ozawa et al 2000;Schmelz et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Following this idea, it has recently been demonstrated that the application of crushed Pieris brassicae L. (Lepidoptera: Pieridae) eggs to Arabidopsis thaliana (L.) activates SAdependent defenses, which function against pathogens, but enhances larval growth of Spodoptera littoralis Boisd. (Lepidoptera: Noctuidae) (Bruessow et al 2010). Yet, little is known about the possible suppression of plant defenses by insect eggs.…”
Section: Introductionmentioning
confidence: 99%
“…SA regulates plant defenses against pathogens, phloem-sucking insects and plant responses to insect oviposition (de Vos et al 2005;Zarate et al 2007;Vlot et al 2009;Bruessow et al 2010). SA alone does not seem to play a signaling role, neither in plant defenses induced by BG insect herbivores (Erb et al 2009a;Pierre et al 2012), nor in BG-AG interactions in Brassica spp.…”
Section: Aboveground and Belowground Inducible Defenses-the Role Of Pmentioning
confidence: 99%
“…The biotic stressors used in this thesis were selected on the basis of the defense signaling pathways they are commonly thought to induce. It is against the crosstalk background described previously that the research contained in this thesis was carried out; while Pieris brassicae caterpillar feeding is primarily activating JA-mediated defenses, all the secondary attackers (P. brassicae eggs, Brevicoryne brassicae aphids, Xanthomonas campestris bacterial pathogens) were chosen because they induce the SA signaling pathway (Ton et al, 2002;Kusnierczyk et al, 2008;Bruessow et al, 2010), though to varying degrees. In the context of dual attack, prioritization of one pathway over another, via crosstalk, would be expected to have a strong effect on subsequent plant responses.…”
Section: Study Systemmentioning
confidence: 99%
“…As voracious feeders, P. brassicae caterpillars pose a major threat to plants as they are capable of entirely defoliating them. The egg stage was also chosen to be included as it has been shown that egg deposition can be sensed by the plant, triggering defense responses (Bruessow et al, 2010) and affecting both plant volatile emission and the foraging behavior of the larval parasitoid of P. brassicae, Cotesia glomerata (Fatouros et al, 2012;Pashalidou et al, 2014).…”
mentioning
confidence: 99%